Toxic changes in some organs of rats exposed to hypervitaminosis A during different gestation period - AL-Rekabi, F. M. K. (The Iraqi Journal of Veterinary Medicine, 2005)
Forty females albino rats divided into four groups, three of them (T1, T2,T3) dosed orally with 10000 IU Vitamin A according to different gestationperiods while the fourth group dosed with distilled water and considered ascontrol (C). Statistical changes in the weight of different treated groups organswere observed specially in the T3 group that represent period of major organofunctionaldevelopment and minor organogensis. Also the histopathologicalstudy revealed sever liver necrosis and sever pulmonary hyperplasia in T1group. Also there was subcutaneous abdominal tumor (fibroma) noticed in onefemale of T2 group. We concluded from our results that high dose of vitamin Amay cause cellular, histological and functional defects with possible cryogeniceffect in some internal organs and tissue.